Experimental study of green hydrogen production applied to gasoline engines with brake load capacity 0,25 kg/cm^2 - Suci Rahmadhani Irawan; Ahmad Ilham Wicaksono; Awaludin Martin (BKS-TM Indonesia, 2025)
Various countries are accelerating their energy transitions due to rising greenhouse gas emissions driving global climate change. The COP26 Conference set targets to limit global temperature rise to below 1.5 °C by 2030 and achieve net-zero emissions by 2050. Hydrogen is considered a promising alternative fuel because it produces only water vapor emissions and reduces dependence on fossil fuels. This study aims to analyze the effect of hydrogen gas, produced through electrolysis, mixed with Pertalite fuel on the performance of an internal combustion engine. The electrolysis process employed an Alkaline Electrolyzer Cell of the wet cell type, using a 30%wt NaOH electrolyte, a 12V power supply, and current variations of 40 A and 50 A. Engine performance parameters were evaluated under a brake load of 0.25 kg/cm². The results showed that at 40 A, the highest HHO gas production rate reached 0.9 Lpm, resulting in a 15.3% increase in effective shaft power, 5.7% thermal efficiency, 6.7% volumetric efficiency, 1.1% AFR, and a 29.06% reduction in BSEC. At 50 A, HHO gas production also reached 0.9 Lpm, with improvements of 18.3% in effective shaft power, 8.6% thermal efficiency, 10.8% volumetric efficiency, 2.84% AFR, and a 40.7% reduction in BSEC. These findings confirm that hydrogen blending enhances engine performance while supporting emission reduction.